2017
DOI: 10.1371/journal.pone.0173782
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonia intracellularis exploits β-catenin/Wnt and Notch signalling pathways during infection of intestinal crypt to alter cell homeostasis and promote cell proliferation

Abstract: Lawsonia intracellularis is an obligate intracellular bacterial pathogen that causes proliferative enteropathy (PE) in pigs. L. intracellularis infection causes extensive intestinal crypt cell proliferation and inhibits secretory and absorptive cell differentiation. However, the affected host upstream cellular pathways leading to PE are still unknown. β-catenin/Wnt signalling is essential in maintaining intestinal stem cell (ISC) proliferation and self-renewal capacity, while Notch signalling governs different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 66 publications
(150 reference statements)
4
26
0
2
Order By: Relevance
“…Similarly, the level of cleaved-CASP3 in lumen of the ileum of vaccinated pigs was, at least in part, reduced to the level observed in sentinel pigs. This may indicate a possible reduction in apoptosis mechanisms as previously described [16] . In contrast, we found that the induction of CP, a marker of neutrophil and macrophage infiltration, was still noticeably expressed in the ileum of vaccinated pigs, perhaps indicating that innate immune cells were actively patrolling the lamina propria at 21 dpc [24] .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Similarly, the level of cleaved-CASP3 in lumen of the ileum of vaccinated pigs was, at least in part, reduced to the level observed in sentinel pigs. This may indicate a possible reduction in apoptosis mechanisms as previously described [16] . In contrast, we found that the induction of CP, a marker of neutrophil and macrophage infiltration, was still noticeably expressed in the ileum of vaccinated pigs, perhaps indicating that innate immune cells were actively patrolling the lamina propria at 21 dpc [24] .…”
Section: Discussionsupporting
confidence: 71%
“…Bacterial loads were also significantly lower in the feces of vaccinated animals, both in terms of reduced severity (bacteria shed per day) and in reduction of the duration of fecal shedding. Reduced proliferation of enterocytes in vaccinated pigs compared to controls, as demonstrated by H&E staining of ileum tissues, coincided with significantly greater numbers of MUC2-expressing goblet cells and IAP-expressing brush border cells than controls indicating a restoration of these essential intestinal cell lineages [6] , [16] , [18] , [19] , [20] . Similarly, the level of cleaved-CASP3 in lumen of the ileum of vaccinated pigs was, at least in part, reduced to the level observed in sentinel pigs.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is now understood that apoptosis is not involved in the pathogenesis of PE, even though contradicting views were reported earlier ( 16 , 21 ). A recent study suggests that a combination of Notch-1 signaling and disruption of the β-catenin/Wnt pathway may be associated with immature crypt cell proliferation ( 24 ). Failure of crypt cells to differentiate into goblet and absorptive cells results in a severe decrease of MUC2 glycoprotein in the affected epithelium at the peak of infection ( 24 ).…”
Section: Introductionmentioning
confidence: 99%